The role of financial distress and fraudulent financial reporting: A mediation effect testing - Reskino Reskino; Aditia Darma (Journal of Accounting and Investment, 2023)
Research aims: This study examines the determinants of fraudulent financial reporting with financial distress as an intervening agent.Design/Methodology/Approach: The banking companies listed on the Indonesia Stock Exchange (IDX) between 2017 and 2020 comprised the study's population. One hundred-four companies comprised the entire sample, which was chosen using purposive sampling. The approach employed in this study was partial least squares (PLS)-SEM.Research findings: The results of this study found that financial targets and audit quality significantly affected financial distress. Financial distress had a significant effect on fraudulent financial reporting. Financial targets and audit quality had no significant effect on fraudulent financial reporting. Furthermore, audit quality significantly affected fraudulent financial reporting through financial distress. Financial targets did not significantly influence fraudulent financial reporting through financial distress.Theoretical contribution/Originality: This study provides literature on the role of financial conditions and good corporate governance in preventing fraudulent financial reporting in banking companies. This study can be an insight for practitioners and academics in Indonesia and internationally. Apart from that, this study contributes to the literature on the occurrence of fraudulent financial statements mediated by financial distress, which is not widely discussed, specifically in the context of the banking industry in developing countries.Practitioner/Policy implication: The practical implication in this research is the importance for investors and creditors to be more vigilant and pay attention to corporate governance and financial conditions to reduce errors in decisions based on financial reports. In addition, the strength of good corporate governance indicates that the supervision carried out by management will take the information conveyed to stakeholders free from material misstatement so that the implementation of good corporate governance can prevent fraud. Research limitation/Implication: This study exclusively includes companies in the banking sector listed on the Indonesia Stock Exchange (BEI) between 2017 and 2020. Out of 46 companies, only 26 may be used as research objects according to the purposive sampling method.